Bright and stable near-infrared Pluronic–silica nanoparticles as contrast agents for in vivo optical imaging. Issue 33 (5th August 2016) - Yan, Lesan; Wang, Huiquan; Zhang, Anqi; Zhao, Calvin; Chen, Yongping; Li, Xingde
Abstract : The IR780@NPs exhibited excellent characteristics for in vivo imaging with a long circulation time and high retention in tumor and sentinel lymph node. Abstract : Near-infrared (NIR) fluorescent nanostructured materials have emerged as novel contrast agents for non-invasive bioimaging. Here we report a class of polymer–silica nanoparticles doped with a NIR fluorescent dye prepared through a facile one-pot strategy. Hydrophobic NIR fluorescent dyes such as IR 780 iodide could be easily encapsulated into the micellar core by the self-assembly of amphiphilic triblock copolymer Pluronic F127. When subsequently adding silane to aqueous solution, nanoparticles with a cross-linked core and a hydrophilic PEG shell were formed. The structure of the as-obtained nanoparticles was confirmed by transmission electron microscopy (TEM) and dynamic light scattering (DLS). The nanoparticles exhibited a well-defined spherical structure with a mean diameter of approximately 30 nm, and excellent monodispersity and stability in aqueous solution. In addition, the photo-stability of IR 780 was significantly improved by encapsulation into the nanoparticles. In vitro MTT assay with cell lines HEK293 and A431 demonstrated that the IR 780 loaded nanoparticles (termed as IR780@NPs) were biocompatible. In vivo sentinel lymph node imaging revealed that the fluorescence intensity and the retention time of the IR780@NPs were clearly superior to those of their constituent free dye, making them amenable to in vivo bioimaging. Further in vivo tumor imaging indicated that IR780@NPs have a longer retention time and much higher accumulation on the tumor site compared to free dyes after intravenous administration. Overall this hydrophilic NIR fluorescent contrast agent exhibits excellent photophysical characteristics and low cytotoxicity, and holds strong promise for a variety of applications including bioimaging and therapy.